The effects of the E3 ubiquitin–protein ligase UBR7 of Frankliniella occidentalis on the ability of insects to acquire and transmit TSWV - Shi,Junxia; Zhou,Junxian; Jiang,Fan; Li,Zhihong; Zhu,Shuifang (PeerJ, 2023)
The interactions between plant viruses and insect vectors are very complex. In recent years, RNA sequencing data have been used to elucidate critical genes of Tomato spotted wilt ortho-tospovirus (TSWV) and Frankliniella occidentalis (F. occidentalis). However, very little is known about the essential genes involved in thrips acquisition and transmission of TSWV. Based on transcriptome data of F. occidentalis infected with TSWV, we verified the complete sequence of the E3 ubiquitin-protein ligase UBR7 gene (UBR7), which is closely related to virus transmission. Additionally, we found that UBR7 belongs to the E3 ubiquitin–protein ligase family that is highly expressed in adulthood in F. occidentalis. UBR7 could interfere with virus replication and thus affect the transmission efficiency of F. occidentalis. With low URB7 expression, TSWV transmission efficiency decreased, while TSWV acquisition efficiency was unaffected. Moreover, the direct interaction between UBR7 and the nucleocapsid (N) protein of TSWV was investigated through surface plasmon resonance and GST pull-down. In conclusion, we found that UBR7 is a crucial protein for TSWV transmission by F. occidentalis, as it directly interacts with TSWV N. This study provides a new direction for developing green pesticides targeting E3 ubiquitin to control TSWV and F. occidentalis.
Keywords: Frankliniella occidentalis; Tomato spotted wilt orthotospovirus; E3 ubiquitin–protein ligase; UBR7; Transmission efficiency